Effect of O-containing functional groups and meso- and micropores on content and re-adsorption behavior of water in upgraded brown coal. (1st December 2019) - Feng, Guorui; Cui, Jiaqing; Niu, Xiaohong; Liao, Junjie; Li, Wen; Bai, Zongqing; Han, Yanna
Graphical abstract: Highlights: CNTs of different pore diameter gave insights into pore effects on UBC water sorption. Pore structures as well as volume of 1–2, 5–10 and 20–50 nm pores of UBC were determined. Forms of water content in UBC containing re-adsorption water were distinguished. Synergistic effects of O-functional groups and 5–10 nm pores on water sorption capacity. 5–10 nm pore volume was an important factor controlling water sorption. Abstract: The original and oxidized CNTs with pore diameters of 1–2, 5–10 and 20–50 nm were used as models to gain insight into the effect of O-containing functional groups and micro- and mesopores on water behavior in UBC. The moisture holding capacity (MHC) and isotherm water adsorption behaviors of both CNTs and UBC were studied and compared. The effects of O-containing functional groups and 5–10 nm pores on water re-adsorption showed synergism with respect to 20–50 nm pores. The water re-adsorption of CNTs with 5–10 nm pores was greatly increased. The mechanism of the synergism was deduced. The specific surface area and the volume of total-, macro-, meso-, and micro-pores as well as the volume of 1–2, 5–10 and 20–50 nm pores of UBC were determined. The re-adsorbed water in UBC was classified into three forms based on binding strength. Correlations between the three forms of water contents and physicochemical parameters of UBC were calculated. The comparison of MHC value with the water adsorption isotherm of UBC at low water vapor pressure indicated that 5–10 nm diameter pore volume was one of the key factors controlling total water re-adsorption capacity. The correlations between the amounts of the three forms of water and physicochemical parameters confirmed this finding. The monolayer water concentration was mainly controlled by the oxygen concentration. Based on the study, we suggest that the 5–10 nm pore should be reduced as much as possible during any brown coal upgrading process for efficient and clean utilization of brown coal.